Assessment of small fiber neuropathy in patients carrying the non‐classical Fabry variant p.D313Y. Issue 5 (19th February 2021) - von Cossel, Katharina; Muschol, Nicole; Friedrich, Reinhard E.; Glatzel, Markus; Ammer, Luise; Lohmöller, Benjamin; Bendszus, Martin; Mautner, Victor‐Felix; Godel, Tim
Abstract: Introduction: The pathophysiological significance of the Fabry‐related, non‐classical variant p.D313Y still remains to be solved. This study assesses the involvement of the peripheral nervous system with respect to small fiber neuropathy and neuropathic pain in female patients carrying p.D313Y. Methods: This study examined nine females carrying the Fabry‐related p.D313Y variant by obtaining skin punch biopsies above the right lateral malleolus. Intraepidermal nerve fiber density was determined for each patient and compared to reference values matched for the patientʼs decade of life and sex. Moreover, each patient was characterized by a detailed neurological examination and by pain assessment via questionnaire. Results: Compared to sex‐matched lower fifth percentile reference values per decade, intraepidermal nerve fiber density was decreased in seven out of nine patients. Four patients reported acral paresthesias and neuropathic pain with an average visual analogue scale score of 7 out of 10 points. Two patients experienced acute pain crises. Six out of seven patients diagnosed with small fiber neuropathy had a their medical history of hypo‐ and/or hyperhidrosis. Discussion: The diagnosis of small fiber neuropathy was made in seven out of nine females carrying the non‐classical variant p.D313Y. Moreover, neuropathic pain and symptoms indicative of autonomic nervous system dysfunction seem to be common findings that may be of clinical significance and may warrant therapeutic intervention.